2016
DOI: 10.1002/tcr.201500250
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Catalyzed Direct Addition of Aryl C-H Bonds to Unsaturated Electrophiles

Abstract: The direct addition of Csp(2) -H bonds onto polar C=C, C=O, and C=N bonds is both synthetically and mechanistically important, because using aromatic C-H substrates in place of organometallic reagents provides a more direct and atom-economical alternative to many important compounds without the pre-generation of organometallic compounds from stoichiometric halides and the unavoidable generation of stoichiometric metal halide waste. In this account, we summarize our contributions to the transition-metal-catalyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 184 publications
1
6
0
Order By: Relevance
“…C-H functionalization has emerged as a core strategy to access synthetically useful structural motifs, many of which are found in drugs and natural products. 1,2 Of the many transition metal catalysts that facilitate this process, Rh(III) catalysts have been demonstrated to be among the most useful due to their unique reactivity and high functional group compatibility. 3 Following the seminal reports of Co(III)-catalyzed C-H functionalization by Kanai and Matsunaga in 2013, 5ac a number of groups including our own have demonstrated that earth abundant Co(III) catalysts can provide analogous reactivity to their second row Rh(III) congeners.…”
mentioning
confidence: 99%
“…C-H functionalization has emerged as a core strategy to access synthetically useful structural motifs, many of which are found in drugs and natural products. 1,2 Of the many transition metal catalysts that facilitate this process, Rh(III) catalysts have been demonstrated to be among the most useful due to their unique reactivity and high functional group compatibility. 3 Following the seminal reports of Co(III)-catalyzed C-H functionalization by Kanai and Matsunaga in 2013, 5ac a number of groups including our own have demonstrated that earth abundant Co(III) catalysts can provide analogous reactivity to their second row Rh(III) congeners.…”
mentioning
confidence: 99%
“…To our delight, reaction of 1-(6-(4-methoxyphenyl)pyridin-3-yl)propan-2-amine (14)with 8a at 100 8 8Cunder an argon atmosphere using 20 mol %o fP d(OH) 2 /C as the catalyst and 3.0 equivalents of sodium formate in water (1 mL;w ith 0.2 mL benzene) for 12 hours gave the CÀH functionalization product 15 a in excellent yield (92 %; Table 4). To our delight, reaction of 1-(6-(4-methoxyphenyl)pyridin-3-yl)propan-2-amine (14)with 8a at 100 8 8Cunder an argon atmosphere using 20 mol %o fP d(OH) 2 /C as the catalyst and 3.0 equivalents of sodium formate in water (1 mL;w ith 0.2 mL benzene) for 12 hours gave the CÀH functionalization product 15 a in excellent yield (92 %; Table 4).…”
Section: Two-in-one Strategy For Palladium-catalyzed C à Hfunctionalimentioning
confidence: 98%
“…To explore the application of the two-in-one strategy for CÀHf unctionalization of other systems,a sw ell as to further exclude the classical Pictet-Spengler reaction pathway,e lectron-deficient aromatic systems,which would not be effective under the standard Pictet-Spengler conditions,w ere investigated. To our delight, reaction of 1-(6-(4-methoxyphenyl)pyridin-3-yl)propan-2-amine (14)with 8a at 100 8 8Cunder an argon atmosphere using 20 mol %o fP d(OH) 2 /C as the catalyst and 3.0 equivalents of sodium formate in water (1 mL;w ith 0.2 mL benzene) for 12 hours gave the CÀH functionalization product 15 a in excellent yield (92 %; Table 4). Other cycloketones also reacted successfully with 14 to give the corresponding annulation products 15 b,c.A ketal group and hetero-ring were tolerated in this catalytic system, affording the annulation products 15 d,e.C ompound 15 f was generated smoothly by reaction with acetone.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…These concepts revolutionized the field of arene functionalization since they avoid not only the formation of unwanted metallic waste but also preactivation of the starting materials. In this context, direct aromatic C–H addition to a carbonyl moiety by transition-metal catalysts can access step- and atom-economical hydroxyalkylation. However, there still remain some problems to be solved in this area. The potentially low nucleophilicity of aryl–transition-metal species requires highly electrophilic coupling partners to achieve satisfactory catalytic turnover.…”
Section: Introductionmentioning
confidence: 99%